2000
DOI: 10.1016/s0370-2693(00)01149-7
|View full text |Cite
|
Sign up to set email alerts
|

Consistent OPE description of gluon two- and three-point Green functions?

Abstract: We perform an OPE analysis of the flavorless non-perturbative gluon propagator and the symmetric three-gluon vertex in the Landau gauge. The first subdominant operator is A µ A µ which can condensate in the Landau gauge "vacuum" although being a non-gauge invariant operator. We neglect all higher dimension operators. Then the gluon propagator and the symmetric three gluon vertex only depend on one common unknown condensate. We propose a consistency check from lattice data. At two loops for the leading coeffici… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
98
0
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(103 citation statements)
references
References 34 publications
(54 reference statements)
4
98
0
1
Order By: Relevance
“…(6) the lattice result g 2 A 2 = 2.76 GeV 2 of Ref. [8], a value compatible with the bound resulting from the discussions of Gubarev et al [9,10] on the physical meaning of A 2 and its possible importance for confinement. As for the contributions O i (1/Q 2 ) (i = A, G) in Eq.…”
Section: Strong Coupling Enhanced By Gluon Condensatessupporting
confidence: 78%
See 2 more Smart Citations
“…(6) the lattice result g 2 A 2 = 2.76 GeV 2 of Ref. [8], a value compatible with the bound resulting from the discussions of Gubarev et al [9,10] on the physical meaning of A 2 and its possible importance for confinement. As for the contributions O i (1/Q 2 ) (i = A, G) in Eq.…”
Section: Strong Coupling Enhanced By Gluon Condensatessupporting
confidence: 78%
“…(3) below] which the running coupling has in the Landau-gauge DS studies [20,28,29,30,31] and the ideas on the possible relevance of the A 2 gluon condensate [2,3,4,5,8,9,10,11,12,13,14]. In the present paper, we give a simplified and more intuitive derivation thereof as follows.…”
Section: Strong Coupling Enhanced By Gluon Condensatesmentioning
confidence: 98%
See 1 more Smart Citation
“…It can be noted that to calculate the coupling more reliably we combined the bare lattice propagators in such a manner that the cut-off dependence is minimal, which prevents the check for the universality of condensates, as gluon and ghost propagators are not to be independently analyzed. However our previous studies in quenched approximation suggested that such universality (even including the three-gluon vertex) is indeed compatible with the numerical data (N f =0) [20,27,28,6,29,7]. This has been also supported by the calculations with N f =2 dynamical flavours [19,30].…”
Section: Introductionsupporting
confidence: 79%
“…[7,19] for N f =0 and N f =2 quark flavours respectively, we calculate the running coupling by equating numerical results and the OPE prediction. The OPE is clearly dominated by the landau gauge gluon condensate A 2 which has been elsewhere very much studied (e.g., see [20,21,22,23,24,25,26]). It can be noted that to calculate the coupling more reliably we combined the bare lattice propagators in such a manner that the cut-off dependence is minimal, which prevents the check for the universality of condensates, as gluon and ghost propagators are not to be independently analyzed.…”
Section: Introductionmentioning
confidence: 99%